Sesquiterpene Lactones as Potential G1/S Phase Cell Cycle Inhibitors: A Molecular Docking Study: Sesquiterpene Lactones as Potential Cell Cycle Inhibitors - Yousaf, Zoufishan; Zaman, Aqsa; Ali, Muhammad; Khan, Muhammad; Ara, Chaman; Shakir, Hafiz Abdullah; Irfan, Muhammad; Khan, Bushra Nisar (Pakistan BioMedical Journal, 2023)
Cell cycle checkpoints play a crucial role in cell division by monitoring the orderly progression of each phase, ensuring accurate completion before advancing to the next stage. They act as quality control mechanisms, pausing the cell cycle when optimal conditions are not met, thereby preventing errors during cell division. Objective: To discover Sesquiterpene Lactones (SLs) as inhibitory compounds targeting Cyclin D1/Cyclin Dependent Kinase 4 (CDK4)- Cyclin Dependent kinase 6 (CDK6) complex and Eukaryotic Transcription Factor 2 protein (E2F-2). Methods: The inhibitory potential of SLs, namely ilicol, eucalyptone, and ascleposide E, was investigated using molecular docking analysis. The docking and visualization of ligand-protein complexes were performed using MGL Tools version 1.5.7, BIOVIA Discovery Studio version 21.1.0, and PyMol version 2.5.2. Additionally, drug likeness and pharmacokinetic properties of SLs were assessed via pkCSM and ADMET analysis. Results: Findings demonstrate that ilicol exhibit most favourable complex with CDK6 having binding energy of –7.8 kCal/mol and inhibition constant 1.81 μM. The visualization of ligand-receptor complexes reveals substantial hydrogen bonding interactions. Conclusions: Current study revealed that novel SLs show favourable drug likeness and promising ADMET profile along with strong inhibitory effect on G1/S regulatory proteins. The potency of SLs is in order of ilicol> ascleposide E>eucalyptone. To further validate the inhibitory effect of ilicol, implementation of comprehensive in vitro and in vivo investigations must be employed for progression of its development as a novel anti-cancer therapeutic.